Bahan Ajar Berbasis Kearifan Lokal Nelayan di Nusantara untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Mahmud, Dini Rosyada (Journal of Innovation and Teacher Professionalism, 2023)
Bahan ajar bagian penting untuk menunjang proses pembelajaran. Indonesia mempunyai kearifan lokal yang beragam contohnya tradisi kehidupan nelayan, namun keterbatasan materi dalam buku peserta didik membutuhkan pengembangan bahan ajar berbasis kearifan lokal. Metode pengembangan menggunakan model ADDIE (Analysis-Design-Development-Implement-Evaluate). Teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi, validasi ahli media, dan angket peserta didik. Teknik analisis data menggunakan kualitatif dari hasil pengamatan observasi, wawancara guru dan peserta didik, saran dan masukan dari dosen ahli bahan ajar. Sedangkan data kuantitatif berupa angka dari pengisian angket. Hasil validasi ahli media bahan ajar diperoleh 92,5 persen dengan kriteria sangat layak digunakan dan validasi ahli materi diperoleh hasil 97,5 persen dengan kriteria sangat layak digunakan juga. Berdasarkan hasil angket penggunaan bahan ajar tentang Potret Kehidupan Nelayan di Kwanyar dapat meningkatkan minat belajar peserta didik. Kata kunci: pengembangan; bahan ajar; kearifan lokal The Teaching Materials Based on Local Wisdom of Fishermen in the Archipelago to Increase the Interest of Elementary School Students in Learning Teaching materials were an important part of supporting the learning process. Indonesia has a variety of local wisdom, for example fishing traditions, but limited material in student books requires the development of teaching materials based on local wisdom. The development method uses the ADDIE (Analysis-Design-Development-Implement-Evaluate) model. Data collection techniques use observation, interviews, documentation, media expert validation, and student questionnaires. The data analysis technique uses qualitative data from the results of observations, interviews with teachers and students, suggestions and input from lecturers who were experts in teaching materials. Meanwhile, quantitative data was in the form of numbers from filling out questionnaires. The validation results from media experts for teaching materials were obtained at 92.5 percent with the criteria being very suitable for use and the validation results from material experts obtained results at 97.5 percent with the criteria also being very suitable for use. Based on the results of the questionnaire, the use of teaching materials about Portraits of Fisherman's Life in Kwanyar can increase students' interest in learning. Keywords: development; teaching materials; local wisdom